Toward an Understanding of Developmental Language Disorder in Adults: Investigating the Relationship Between Cognitive Abilities and Linguistic Outcomes. - Blake, Ashley; Dąbrowska, Ewa; Llompart, Miquel (Journal of Speech, Language & Hearing Research, 2025)
Purpose: There is a growing body of research on developmental language disorder (DLD), but very few studies have focused on the role of cognitive abilities in adulthood. The present study explored the relationship between cognition and language in adults with and without DLD. Method: Sixty participants, 30 language typical (LT) adults and 30 with DLD, completed a battery of online cognitive and language assessments. Cognitive tasks included language analytic ability (the ability to recognize the grammatical functions of sentence elements), nonverbal IQ, explicit learning of form-meaning pairings, implicit statistical learning, and speed of automatization. Language assessments included two grammar tasks (assessing morphosyntax) and vocabulary. Accuracy and reaction time measures were obtained for all tasks. Results: Between-group differences demonstrated that language remains an area of difficulty for adults with DLD. Language analytic ability was a significant predictor of grammatical and vocabulary knowledge in the LT group and of grammar in the DLD group. In addition, we found that explicit learning of form-meaning pairings predicted linguistic outcomes in adults with DLD. We found small or no differences for all the other cognitive abilities; this is in line with previous studies that report a relative "catch up" in cognitive abilities in adults with DLD. Response times for the DLD group were slower in both linguistic and nonlinguistic tasks. Conclusions: Our results demonstrate that language difficulties in DLD persist into adulthood. Regarding cognitive measures, we show that language analytic ability is a key predictor of linguistic outcomes in both groups, and explicit learning of form-meaning pairings predicts grammar and vocabulary in the DLD group. These findings have important implications for clinical interventions, as they suggest that both implicit (fast, effortless, and unconscious) and explicit (slow, effortful, and conscious) processes are relevant to language. In addition, adults with DLD may require additional processing time in cognitive and linguistic tasks.